ANALISIS KRITIS HAKIKAT DAN SEJARAH PENCIPTAAN MANUSIA DALAM PERSPEKTIF TEOLOGI DAN BIOLOGI - Pamungkas, Sukma; Diah Novita Fardani (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
The creation of humans has long been a subject of debate between theological and scientific perspectives. This article aims to explore the history of human creation using a comparative approach that integrates both theological and biological viewpoints. In theology, humans are viewed as special beings created with moral and spiritual purposes, serving as stewards of the Earth with ethical responsibility for maintaining ecological balance and fostering a relationship with the Creator. In contrast, biology explains the origin of humans through a complex and gradual process of evolution, portraying humans as a product of adaptation to ever-changing environments. The methodology employed in this study is a comparative approach, analyzing and contrasting theological perspectives found in religious texts with scientific theories of evolution, such as those proposed by Darwin and recent findings in genetics. A comparison with previous works shows that although these two approaches are often seen as conflicting, each contributes significantly to our understanding of human nature. The findings of this study conclude that integrating both perspectives offers a more holistic understanding of humans as beings with not only physical and cognitive dimensions, but also profound moral and spiritual aspects. Thus, these two viewpoints complement each other, providing a more comprehensive picture of human origins and purpose in life.